2020
DOI: 10.1002/acp.3636
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alcohol and weapon presence on eyewitness memory and confidence

Abstract: Summary In this quasi‐experimental field study, bar drinkers (0.00–0.23% blood alcohol content) viewed a photographic sequence in which a male took a laptop from a helpdesk assistant, either on loan or at gunpoint. Following a brief retention period, participants answered 20 multiple‐choice questions about the male, his actions, and details of the scene, then attempted to identify him from a simultaneous target‐present or target‐absent line‐up. Alcohol was associated with a reduction in correct identifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 72 publications
(135 reference statements)
1
21
0
Order By: Relevance
“…That Harvey et al (2020) found no effect of witness intoxication on scene memory was not a big surprise as such null effects are relatively common in the applied alcohol and memory literature. The absence of a WF effect is more unusual, particularly as the design of that study was a replication of the seminal Loftus et al (1987) WF demonstration.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…That Harvey et al (2020) found no effect of witness intoxication on scene memory was not a big surprise as such null effects are relatively common in the applied alcohol and memory literature. The absence of a WF effect is more unusual, particularly as the design of that study was a replication of the seminal Loftus et al (1987) WF demonstration.…”
Section: Introductionmentioning
confidence: 94%
“…The absence of a WF effect is more unusual, particularly as the design of that study was a replication of the seminal Loftus et al (1987) WF demonstration. Here, we test the possibility that both null effects are attributable to three limitations of the Harvey et al (2020) design. First, the multiple‐choice memory questionnaire was limited by the absence of a “do not know” response option for each item.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations